DESIGN, SIMULATION AND ANALYSIS OF A HYBRID-TYPE (PV/T) SOLAR AIR HEATER FOR HIGH PERFORMANCE - Pramod kumar N; B. Sadashive Gowda (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with the numerical analysis of a Hybrid-Type (PV/T) Solar Air Heater and a study on the effect of various design parameters that enhance the performance of the system. The heat transfer improvement in general may be achieved by increasing the heat transfer coefficient or by increasing the surface area or by increasing both. The main objective of the present work is to determine the optimum air mass flow rate at which PV/T systems are to be operated and to develop an optimal design of a hybrid type (PV/T) solar air heater that shows better performance at various heat fluxes due to solar radiation. This study determines the set of design parameters which lead to the best annual yield of the system. In this study of a hybrid type (PV/T) solar air heater ICEM CFD (ANSYS) is used to obtain the optimum results, thereby increasing the efficiency of the system